2010
DOI: 10.1152/japplphysiol.00707.2010
|View full text |Cite
|
Sign up to set email alerts
|

Countermeasures against lumbar spine deconditioning in prolonged bed rest: resistive exercise with and without whole body vibration

Abstract: To evaluate the effect of short-duration, high-load resistive exercise, with and without whole body vibration on lumbar muscle size, intervertebral disk and spinal morphology changes, and low back pain (LBP) incidence during prolonged bed rest, 24 subjects underwent 60 days of head-down tilt bed rest and performed either resistive vibration exercise (n = 7), resistive exercise only (n = 8), or no exercise (n = 9; 2nd Berlin Bed-Rest Study). Discal and spinal shape was measured from sagittal plane magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 38 publications
8
76
0
Order By: Relevance
“…The gellike material (d) is fat tissue Eur Spine J (2016) 25:144-154 145 could explain increases in spinal length despite swelling of the IVD, but flattening of the lumbar lordosis has not been consistently found in bed rest studies. At the end of prolonged bed rest, decreases [17,21], no change [14,22], and increases [16] of the lumbar lordosis have been seen. This physical mechanism (Fig.…”
Section: What Are the Likely Mechanisms?mentioning
confidence: 96%
See 1 more Smart Citation
“…The gellike material (d) is fat tissue Eur Spine J (2016) 25:144-154 145 could explain increases in spinal length despite swelling of the IVD, but flattening of the lumbar lordosis has not been consistently found in bed rest studies. At the end of prolonged bed rest, decreases [17,21], no change [14,22], and increases [16] of the lumbar lordosis have been seen. This physical mechanism (Fig.…”
Section: What Are the Likely Mechanisms?mentioning
confidence: 96%
“…2 Expansion of the lumbar L4/5 IVD due to spaceflight simulation (bed rest). MR images of 23 subjects of an earlier 60-d bed rest study [21], and have not been published previously. In this dataset, whole IVD volume increased by mean (SD) 6.0 (3.3) %, IVD height increased by 7.0 (3.6) % and the anteroposterior IVD dimension decreased by 1.6 (1.9) %.…”
Section: Muscle Changesmentioning
confidence: 99%
“…Alternatively, astronauts are quite busy with mission tasks, and one may argue that their usage of their neck muscles in these tasks may well prevent atrophy. Furthermore, predicting muscular changes in bed rest on the basis of existing findings in spaceflight can be difficult: the psoas muscle at the lumbar spine was observed to atrophy after spaceflight (10), but studies in bed rest have shown either significant (2,32) or nonsignificant (3,8,23) increases in the size of this muscle. Thus it is difficult to predict, on the basis of existing data, whether muscle atrophy may occur at the neck during bed rest.…”
mentioning
confidence: 99%
“…Lumbar spine lengthening and hypertrophy of the lumbar invertertebral discs is seen in prolonged bed rest (2). The question remains open as to whether similar hypertrophy occurs at the cervical and thoracic intervertebral discs.…”
mentioning
confidence: 99%
“…Countermeasure studies have been conducted during bed rest (e.g. Belavy et al, 2010;Blottner et al 2006;Miokovic et al, 2011), which provides an analogue of microgravity; a useful tool given the methodological constraints of conducting studies inflight (see below regarding methodological challenges). Members of the Reconditioning Topical…”
Section: Exercise-based Countermeasures To Minimise Effects Of Microgmentioning
confidence: 99%